(3EQTGO GdZGhi aj eSGdc GdMGhjs - (3TQa GdOjf ESeGYjd Hf CHj HcQ Hf YHO Gddg Hf EHQGgje GdebQj GdTQLj GdMSjfj, GdTGhQj GdRHjOj Gdjefj,J (B837 (3g` s ((3YHO GdUeO Hf SGde Hf CeGQc GdMQGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dGJMUi ehGgHg hHYO agPG eNJUQ Mhi GdePgH fWbkG hVefkG , NejU ef GddaX HWjf ef GdeYfi , ENJUQJ ajg GdMGOi s
(3BNQgG (B:s
(3HGH fe CJJ HeNWW dG ai fbd edc Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YeQ Hf CMeO GdYehQi GdYGeg MQjVg s
Keywords: (3Gdabg GdTGaYjs